On boundedness and compactness of a certain class of kernel operators - Elena P. Ushakova (Journal of Function Spaces and Applications)
New conditions for Lp[0,∞)-Lq[0,∞) boundedness and compactness (1<p, q<∞) of the map f→w(x)∫a(x)b(x)k(x,y)f(y)v(y)dy with locally integrable weight functions v,w and a positive continuous kernel k(x,y) from the Oinarov’s class are obtained.